THE EFFECT OF WORK ETHICS ON JOB PERFORMANCE: AN ASSESSMENT OF SELECTED FEDERAL MINISTRIES IN THE FEDERAL CAPITAL TERRITORY OF NIGERIA (Malaysian Management Journal, 2025)
Employee behaviour at work can be ethical or immoral, and is typically linked to work ethics. The purpose of this study is to investigate the relationship between government officials' performance and work ethics. In this study, work ethics and their effect on performance are assessed using a structural model. The methodology utilized was the exploratory type. A total of 384 self-administered questionnaires were distributed to respondents who were selected using a convenience sample technique. Using a six-point Likert scale, only 157 returned self-administered questionnaires were given to 157 respondents who were chosen at random from administrative positions in several Nigeria Federal Ministries situated in the Federal Capital Territory. The Multidimensional Job Ethics Profile (MWEP) was the tool used to evaluate ethical behaviour in the workplace. The findings obtained support the validity and accuracy of the structural model as a means of assessing the connection between performance and work ethics. The study concluded that work ethics have a significant influence on workplace performance, emphasising their critical role in enhancing job performance.